2022
DOI: 10.1186/s40635-022-00454-7
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in cardiac function, inflammation and injury during early polymicrobial sepsis

Abstract: Background Sex differences in sepsis are underexplored and incompletely understood. Cardiac function in early sepsis is pivotal in determining survival; hyperdynamic left ventricular ejection fraction is associated with higher mortality. Female sex may be cardioprotective, but variable experimental findings have not controlled for hypovolaemia. Sex-specific local cardiac versus peripheral inflammation in causing cardiovascular dysfunction also remain unclear. We therefore examined whether there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In line with our findings, Wearing et al reported elevated BNP and ANP levels in male mice [ 46 ]. In addition, it has been demonstrated that a decrease in oxygen pressure led to increased synthesis of natriuretic peptides and that male mice were susceptible to higher cardiac natriuretic peptide levels compared to female mice during myocardial injury [ 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, Wearing et al reported elevated BNP and ANP levels in male mice [ 46 ]. In addition, it has been demonstrated that a decrease in oxygen pressure led to increased synthesis of natriuretic peptides and that male mice were susceptible to higher cardiac natriuretic peptide levels compared to female mice during myocardial injury [ 47 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported fundamental data regarding the cardiac response to sepsis and sex dimorphism [ 25 , 26 , 27 ]. Estrogen modulates several acute injury-related myocardial responses.…”
Section: Animal Modelsmentioning
confidence: 99%